Public Procurement and Mediation to Facilitate Procedures for the preservation of World's Cultural Heritage - Sideri, Maria (Technical Annals, 2023)
All levels of legislation from national rules to international Treaties include provisions for heritage procurement and alternative dispute resolution. Each law has got its own scope and field of application: some of those are obligatory, with direct effect and supreme. Practitioners thus need to apply the right texts for the conclusion of public contracts and for the resolution of their disputes. Mediation is being proposed as a very modern and flexible tool for disputes’ settlements arising in a contest. Some examples of successful public procurement may be found here and a superficial approach to the Hagias-Sofia project.